2009
DOI: 10.2337/dc08-2318
|View full text |Cite
|
Sign up to set email alerts
|

Immune Mediators in Patients With Acute Diabetic Foot Syndrome

Abstract: OBJECTIVESubclinical inflammation is an important risk factor for type 2 diabetes and diabetes complications. However, data on the association between inflammation and acute diabetic foot syndrome are scarce. The aim of this study was to compare systemic immune mediators in diabetic patients with and without an ulcer and to identify modulating factors.RESEARCH DESIGN AND METHODSCirculating levels of acute-phase proteins, cytokines, and chemokines were measured in diabetic patients with an ulcer (n = 170) and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 25 publications
8
70
1
Order By: Relevance
“…Although only 25 (56% of the 45 patients that reported smoking) suffered an amputation, a history of smoking is important in the development of diabetic foot ulcers because of the endothelial damage it produces. In particular, it has been reported that smokers suffer more from diabetic foot ulcers and have a higher risk of amputations than non-smokers [29,35,37,47,48]. …”
Section: Discussionmentioning
confidence: 99%
“…Although only 25 (56% of the 45 patients that reported smoking) suffered an amputation, a history of smoking is important in the development of diabetic foot ulcers because of the endothelial damage it produces. In particular, it has been reported that smokers suffer more from diabetic foot ulcers and have a higher risk of amputations than non-smokers [29,35,37,47,48]. …”
Section: Discussionmentioning
confidence: 99%
“…The analysis of a complete set of mediators can therefore be considered to be of more value than the single analysis of only one single analyte (Gardy et al 2009;de Jager et al 2003). Although protein microarray technology has been successfully applied for the analysis of multiple analytes in complex biological mixtures -such as plasma, serum, urine and cerebrospinal fluid-publications using protein arrays for the analysis of wound status are rare (Hsu et al 2008;Weigelt et al 2009;Craig-Schapiro et al 2011;Swain et al 2011). For instance, Grimstad et al measured the concentration of 27 different cytokines in wound fluid derived from acute wounds using a bead-based system (Grimstad et al 2011).…”
Section: Protein Arrays For the Analysis Of Minute Sample Amountsmentioning
confidence: 99%
“…Consecutively, a variety of immune mediators -including acute phase proteins, cytokines and chemokines-were examined in the plasma of patients with diabetic foot syndrome. These markers included CRP and fibrinogen as well as IL-6, IL-8, IL-18, macrophage inflammatory protein 1 (MIP1), interferon -inducible protein-10 (IP10), macrophage migration inhibitory factor (MIF), macrophage chemoattractant protein 1 (MCP1) and RANTES (Weigelt et al 2009). Both of the studies just cited were able to connect the occurrence of certain systemic inflammatory markers with the presence of infection in the diabetic foot.…”
Section: Infection In the Diabetic Footmentioning
confidence: 99%
“…Weigelt et al [34] analyzed the possible relationship between foot ulcers and immune status in diabetic subjects with and without foot ulcers by evaluating some immune mediators. Authors reported how circulating levels of some inflammatory markers such as acute-phase proteins, cytokines, and chemokines were higher in patients with diabetic foot.…”
Section: Inflammation Markers In Patients With Dfsmentioning
confidence: 99%